Mycoplasma pneumoniae Infection: An Updated Narrative Review - Kusuma Wardani, Ni Made Ayu Mulia (HM Publisher, 2024)
Pneumonia cases in China, which rose sharply from October to November 2023, have received particular attention in the world of health. Chinese authorities said the trigger was not a new pathogen, one of which was Mycoplasma. Mycoplasma pneumoniae is a bacteria that can cause disease by damaging the lining of the respiratory system. Mycoplasma pneumoniae infection can occur in all age groups, especially at school and pre-school age. Most studies report that the age group that most often experiences Mycoplasma pneumoniae infection is those aged over 5 years. The importance of recognizing symptoms and providing adequate therapy is very necessary to treat pneumonia caused by Mycoplasma pneumoniae infection.